Library and bibliographic classification, XXIst century: results of the first decade, plans for the second one - E. R. Sukiasyan (Библиосфера)
The author presents the results of work on the development of the National Classification System of Russia – Library and Bibliographic Classification done during the first decade of the XXI century: the publications are listed, the methodical provision of using tables in the libraries is given. Characterized are the tasks facing the team of developers in future.